2012
DOI: 10.1177/1086026612440097
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning From Endgame to Sustainability

Abstract: This article engages with Peter Barnes’s work on commons trusts as a model to confront mounting social and ecological crises. The authors begin by locating Barnes’s model within the context of other approaches to this issue and by describing the main elements of his work and applying them to the case of carbon reduction strategies. Throughout, the article highlights the key strengths, limitations, and implications of Barnes’s model. Although Barnes offers a proposal for institutional change that could democrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This situation was designed as an analogue to open access management of commons (Brownlee & Kueneman, 2012). Both dilemma type (traditional/consumption vs. reverse/disposal) and cost (money vs. time) were manipulated using scripts.…”
Section: Present Studymentioning
confidence: 99%
See 3 more Smart Citations
“…This situation was designed as an analogue to open access management of commons (Brownlee & Kueneman, 2012). Both dilemma type (traditional/consumption vs. reverse/disposal) and cost (money vs. time) were manipulated using scripts.…”
Section: Present Studymentioning
confidence: 99%
“…Scientists have identified a list of boundaries beyond which planetary systems are unreliable and most involve global commons such as atmospheric carbon, ocean acidification, ozone depletion, global freshwater, and chemical pollution (Hoffman & Jennings, 2015). Unfortunately, research on commons management indicates that such global commons are the most difficult to use sustainably (e.g., Berkes, 2009;Brownlee & Kueneman, 2012;Feeny, Berkes, McKay, & Acheson, 1990). Hardin (1968) suggested that commons are difficult to manage sustainably because of economic rationality: An individual using the commons beyond their share of the resource's capacity (e.g., overfishing) retains all of the profit from their additional use while the cost (e.g., reduction of breeding capacity below replacement) is shared by all users.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, most loss aversion research investigates personal choices, ones that would directly impact the chooser, such as preferred investments or health treatments (e.g., Weber, Blais, & Betz, ). However, at least in democratic countries, many important decisions involve public or collective resources––things we share such as public institutions, infrastructure, and the natural environment (e.g., Brownlee & Kueneman, ). The purpose of the present study was to examine whether a loss frame impacts decisions about public resources and actions in addition to more personal decisions.…”
Section: Goal Framing In Public Issue and Action Decisionsmentioning
confidence: 99%